Certified to succeed? Multilevel analysis of the effects of teacher certification on educator well-being and student outcomes in Indonesia - Nawas, Abu; Darmawan, I. Gusti Ngurah; Maadad, Nina (Teaching and teacher education, 2025)
The teacher certification program in Indonesia has been implemented for two decades, yet its impact on teacher well-being, student well-being, and educational outcomes remains underexplored. This study examines these relationships using multilevel path analysis on data from 1319 secondary school students across 64 classrooms. Results show certification positively affects teacher job satisfaction (β = .45) and reduces student learning anxiety (β = −.11). Indirect effects on achievement were mediated by teacher efficacy, collaboration, and motivation. However, no significant effects on student well-being were found, highlighting the need to reassess the certification framework to better support both teachers and students. •Certified teachers have high job satisfaction and reduce student learning anxiety.•Teacher certification affects teacher well-being and student learning outcomes.•No direct and indirect effects of teacher certification on student well-being.